2011
DOI: 10.1074/jbc.m110.211649
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors of a Shikimate Pathway Enzyme from Mycobacterium tuberculosis

Abstract: Tuberculosis remains a serious global health threat, with the emergence of multidrug-resistant strains highlighting the urgent need for novel antituberculosis drugs. The enzyme 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase (DAH7PS) catalyzes the first step of the shikimate pathway for the biosynthesis of aromatic compounds. This pathway has been shown to be essential in Mycobacterium tuberculosis, the pathogen responsible for tuberculosis. DAH7PS catalyzes a condensation reaction between P-enolpyruvate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 45 publications
(23 reference statements)
2
56
0
Order By: Relevance
“…1 The pathway has received considerable attention due in large part to the identification of one of its enzymes, 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase, as the cellular target of the herbicide, glyphosate (N-(phosphonomethyl) glycine). 2 While a number of studies have sought to identify inhibitors of other enzymes in the pathway, [3][4][5][6][7][8][9] a relatively small number of compounds have been identified that block the pathway's fourth reaction, the NADPH-dependent conversion of 3-dehydroshikimate to shikimate. [10][11][12] This reaction is catalyzed by shikimate dehydrogenase (AroE).…”
Section: Introductionmentioning
confidence: 99%
“…1 The pathway has received considerable attention due in large part to the identification of one of its enzymes, 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase, as the cellular target of the herbicide, glyphosate (N-(phosphonomethyl) glycine). 2 While a number of studies have sought to identify inhibitors of other enzymes in the pathway, [3][4][5][6][7][8][9] a relatively small number of compounds have been identified that block the pathway's fourth reaction, the NADPH-dependent conversion of 3-dehydroshikimate to shikimate. [10][11][12] This reaction is catalyzed by shikimate dehydrogenase (AroE).…”
Section: Introductionmentioning
confidence: 99%
“…These amino acids are essential nutrients in the animal diets, and their biosynthetic pathways are prime targets of antimicrobial drugs and plant herbicides (e.g., glyphosate) (Schönbrunn et al, 2001;Reichau et al, 2011). Phe and Tyr also serve as precursors of various aromatic natural products such as pigments, antibiotics, and alkaloids (Bentley, 1990;Maeda and Dudareva, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The initial nucleophilic attack of PEP on E4P is predicted to be promoted by coordination of the E4P aldehydic oxygen to the essential divalent metal ion, giving an oxocarbenium ion intermediate 4 ( Fig. 1) [3,6]. The addition of an active site nucleophilic water results in a phosphohemiketal tetrahedral intermediate 5, which forms acyclic DAH7P on the elimination of phosphate.…”
Section: Introductionmentioning
confidence: 98%
“…In mammals these essential metabolites are obtained from dietary sources, and the enzymes of the shikimate pathway are absent. Therefore, the enzymes of this pathway have been identified as promising targets for the development of new antibacterial therapeutics [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation